Olive Mill and Olive Pomace Evaporation Pond’s By-Products: Toxic Level Determination and Role of Indigenous Microbiota in Toxicity Alleviation - Houda Ben Slama; Ali Chenari Bouket; Faizah N. Alenezi; Ameur Khardani; Lenka Luptakova; Armelle Vallat; Tomasz Oszako; Mostafa E. Rateb; Lassaad Belbahri (Applied Sciences, 2021)
Diverse vegetable oils are extracted from oleagenic trees and plants all over the world. In particular, olive oil represents a strategic socio-economic branch in the Mediterranean countries. These countries use either two or three-phase olive oil extraction systems. In this work, we focus on the by-products from three-phase olive oil extraction, which are the liquid olive mill wastewater (OMW) and the solid olive mill pomace (OMP) rejected in evaporative ponds. The disposal of this recalcitrant waste poses environmental problems such as the death of different species of insects and animals. In-depth ICP-OES analysis of the heavy metal composition of OMW and OMP revealed the presence of many metals ranging from non-toxic to highly toxic. The LC-HRMS characterization of these by-products indicated the presence of several secondary metabolites harmful to humans or to the environment. Thus, we aimed to identify OMW and OMP indigenous microbiota through metagenomics. The bacterial population was dominated by the Acetobacter (49.7%), Gluconobacter (17.3%), Gortzia (13.7%) and Nardonalla (5.3%) genera. The most abundant fungal genera were Nakazawaea, Saccharomyces, Lachancea and Candida. These microbial genera are responsible for OMW, OMP and soil toxicity alleviation.